(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to demonstrate the impact of the administrative expenses of the marine insurance department on the profitability of insurance companies and to present the basic concepts of administrative expenses and profitability and the importance of this portfolio in the insurance sector, thus identifying the most important criteria that can be applied to measure it within the government research sample companies (National Insurance Company and the Iraqi Insurance Company) and Al-Hamra Insurance Company (Al-Hamra Insurance Company) and Dar Al Salam Insurance Company) As the research problem lies in the weak demand for marine insurance in Iraq and thus affects the profitability of insurance companies. As for the research method, the descriptive analytical approach was used for the purpose of taking note of all the essential aspects, and statistical methods were used (arithmetic mean, standard deviation, coefficient of variation and testing the correlation between the dependent variable) The company’s profitability) and the independent variable (administrative expenses) and the impact test using the statistical program (SPSS23) to extract the administrative expenses of the marine insurance department for each company for the period from (2011 – 2020) and using the profitability represented by the net profit of the portfolio. The data was collected through the field experience of the researcher in the research sample companies The research concluded that there is no statistically significant effect of the administrative expenses of the marine insurance portfolio on the profitability of the research sample companies.